Penerimaan Pajak Rumah Kos di Kota Pekanbaru saat Pandemi Covid-19 - Sonia Sischa Eka Putri (Owner : Riset dan Jurnal Akuntansi, 2022)
Boarding houses are one of the fastest growing forms of business in the city of Pekanbaru, where boarding houses are one of the fastest growing businesses and have an impact on local tax revenues. The boarding house tax contributes to regional income in order to increase the Pekanbaru city's regional budget with a tax rate of 2.5%. This study aims to see the impact of taxation on boarding houses during the COVID-19 pandemic. This study uses a descriptive qualitative approach. data were obtained from 15 informants with the criteria of having a boarding house with more than 10 rooms. This research was conducted by observing and interviewing the owners of the boarding house in order to find out the understanding of the obligations of business owners to their business taxes. The results of the study show that boarding house owners in 2020-2021 cannot pay their tax obligations as usual due to the pandemic, boarding houses have a very strong impact, tenants who are usually workers and students do not use boarding houses during the pandemic. In addition, regional tax revenues have also decreased in almost all tax objects, seen from boarding house taxation, income has decreased significantly so that regional budgets are also affected due to the COVID-19 pandemic.